Estimation of the world market and application of nanomaterials in the aerospace industry - Malyshev, Viktor; Gab, Angelina; Kovalenko, Viktoriia; Lipskyi, Yurii; Shakhnin, Dmytro (Technology audit and production reserves, 2024)
The object of the study is the global aerospace market status, segment analysis, dynamics, competition, and prospects. The methods of searching and analyzing literature data, summarizing, systematizing, and visualizing data with diagrams are used. The aerospace industry is at the forefront of technological innovation and is constantly searching for new advanced materials to improve productivity, efficiency, and safety. The aerospace market encompassing the design, manufacture, and maintenance of aircrafts, space vehicles, and related systems. It includes the commercial and military sectors, as well as the space exploration field. The world market of the aerospace industry was studied. Factors affecting the market positively and negatively were identified. According to the global aerospace market segmentation by vehicle types, the leading position in 2023 was occupied by the commercial aircrafts segment with a share of 63.4 %; by the vehicle size – by the narrow-body aircraft segment (72.4 %); by the end consumer – by the private sector segment (65.4 %); by operation – by manually operated aircrafts segment (79.4 %); and by geographic regions – by the North American segment (47.3 %). The main strategic trends and directions of the further aerospace market development are presented. The world market of aerospace materials was studied. Factors affecting market dynamics are identified, and market challenges are highlighted. According to the world aerospace market segmentation by the materials types, the leading place in 2022 belonged to the composite materials segment with a share of 69 %; by the aircraft type – to the commercial aircrafts segment (51 %); and by geographical regions – to the European segment (35.0 %). The trends of the sustainable aerospace industry development are summarized: modern aircraft design, use of sustainable aviation fuel, urban air mobility, modern traffic technology, and air transportation management optimization. For each trend, possible actions leading to changes in the aerospace industry are considered. The question of the nanomaterials use in the space industry is considered. Some characteristics and possibilities of application of nanocomposite materials, nanocoatings, nanofluids, nanosensors, and carbon nanotubes, as well as examples of the nanomaterials application in aircraft components are given. The industry problems are identified, and their possible solutions are given.